Osman Şahin’in Eserlerindeki Halk Bilimi Unsurları - Tahan, Ömer (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
In this study twenty two books of Osman Şahin, who contributed to Turkish Literature especially by concentrating on country life and problems, are studied most particularly, and folkloric components are analyzed. Ethnographic research methodology is prefered in our study. The reason to use this methodology resulted from the fact that the culture of people mentioned in these stories is examined in our study. He contributed to the last period of our Literature with his language and wording, realistic approach, his concretisations, and his works in which locations where his stories take place don’t contradict with its characters and we can listen to them by their own dialect characteristics. We confined our study to the main heading of language used by people, transition periods, traditions/customs (manners-customs-morals), folklore, feastsceremonies- celebrations, beliefs, performance, entertainment, folkloric dance and sport, clothes, ornament, folkloric art, professions and handicraft, folkloric architecture, folkloric cookery keeps curiosity and attention of the reader constantly alive. Our study is composed of two chapters. First chapter is on life of Osman Şahin and his literary personality. Second chapter constitutes the main part of the study. As we mentioned above, folkloric components in twenty two books of Osman Şahin are analysed by including also his forms of utilisation. Also, information about folklore derived from books, journals, articles, proceedings, symposium, thesis and onlines sources together with our comments are in this chapter as well. In conclusion part, we put our personal comments about the author and his works according to the information we obtained. In references part, all sources we used and all books of author we studied are given in line with Institure’s format. Osman Şahin set foot on many regions of Anatolia, he observed the modes of living of people, their customs-traditions, language and dialect characteristics, and used them one by one in his books according to subject, place and characters. The purpose of our dissertation is to bring his contributions to Folklore to light. We had knowledge about unique modes of living of people living in Anatolia, their manners and traditions. Keywords: Osman Şahin, his life and literary personality, Components of Folklore

ÖZ: Türk Edebiyatı’na özellikle kır hayatı ve sorunları üzerinde yoğunlaşarak katkı vermiş olan Osman Şahin’in yirmi iki kitabı üzerinde durulmuş, bu çalışmada halkbilimi unsurları incelenmiştir. Çalışmamızda etnografik araştırma yöntemi kullanılmıştır. Bu yöntemin kullanılmasının sebebi; çalışmamızda öykülerde geçen halkın kültürünün irdelenecek olmasıdır. Edebiyatımızın son dönemine; dil ve üslubu, öykülerindeki reel yaklaşımı, somutlamaları ve öykülerinin geçtiği mekânların kahramanlara tezat düşmediği, onları, onların ağız özelliği ile dinleyebildiğimiz eserleri ile katkı vermiştir. Okuyucuda merak ve ilgi unsurlarını kıyamda tutan Osman Şahin’in kitaplarında geçen halkın kullandığı dil, geçiş dönemleri, gelenek, görenek (örf, adet, töre), halk bilgisi, bayramlar, törenler, kutlamalar, inanışlar, oyun eğlence, halk oyunları ve spor, giyim, kuşam, süsleme, halk sanatı, meslek ve zanaatları, halk mimarisi, halk mutfağı ve son olarak imece ana başlıklarıyla çalışmamızı sınırlandırdık. Çalışmamız üç bölümden oluşmaktadır. İlki Osman Şahin’in hayatı ve edebi kişiliği üzerinedir. İkinci bölüm çalışmanın asıl bölümünü oluşturmaktadır. Osman Şahin’in yukarıda da zikrettiğimiz gibi yirmi iki kitabındaki halkbilimi unsurları ve incelenen kitaplardaki kullanım şekillerine de yer verilmek suretiyle kaleme alınmıştır. Aynı zamanda halkbilimi ile ilgili olarak yararlanılan kitap, dergi, makale, bildiri, sempozyum, tez ve internetten edinilen bilgiler ışığında Osman Şahin’in eserleri irdelenmeye çalışılmıştır. Sonuç son bölümümüzdür. Sonuç bölümünde edindiğimiz bilgiler doğrultusunda yazarın eserleri hakkında şahsi yorumlarımızı yazdık, kaynaklar bölümünde ise, yararlandığımız tüm kaynakları ve yazarın incelenilen tüm kitapları Enstitü formatına göre verilmiştir. Osman Şahin, Anadolu’nun birçok bölgesine ayak basmış, halkın yaşam şekillerini, gelenek-göreneklerini, Anadolu’da kullanılan ağız özelliklerini gözlemlemiş bunları tek tek kitaplarında konu, mekân ve kahramanlarına göre kullanmıştır. Tezimizin amacı; Osman Şahin’in eserlerine yansıyan Halkbilimi unsurlarını gün yüzüne çıkarmak olmuştur. Anahtar Kelimeler: Osman Şahin, Hayatı ve Edebi Kişiliği, Halkbilimi Unsurları
Türk Dili ve Edebiyatı Dalında Yüksek Lisans Tezidir. Tez (Yüksek Lisans)--Doğu Akdeniz Üniversitesi, Fen ve Edebiyat Fakültesi, Türk Dili ve Edebiyatı Bölümü, 2017. Tez Danışmanı: Yard. Doç. Dr. Elnara Bashirova
Keywords: Türk Dili ve Edebiyatı; Şahin, Osman-Yazar-İnceleme; Osman Şahin; Hayatı ve Edebi Kişiliği; Halkbilimi Unsurları